Pokok-Pokok Bahasan Kebahasaan dalam Kajian Antropologi Bahasa - Hendarto Supatra (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Linguistic anthropology or ethnolinguistics is a branch of anthropology with language in use or speech as it’s object of study. In another way it is the study of a language as a cultural resource and speaking as a cultural practice. This science with such a definition can be traced back to the Sapir and Whorf hypothesis, concerning with theory of linguistic relativity and theory of linguistic determinism. It is a matter of conceptual world based on perception or more specific a representation of reality (real world). Linguistic anthropology with such a focus of study no need to be done only in primitive society but in modern society as well and in internal language since there are many sub-societies in a language society. The method in this study is what is called thick description that must be carried out using grounded research. The issues and topics that are at the core of this research such as the politics of representation, the legitimation of power, the cultural basis of racism and ethnic conflict, the relationship between ritual performance and the forms of social control, speech in ceremonies, ritual, meeting, and so on.